THE PORTRAYAL OF FEMALE VILLAINS: A REPRESENTATION STUDY ON CRUELLA - Traesar, Livia; Saktiningrum, Nur (Pengkajian Amerika, Universitas Gadjah Mada, 2024)
The portrayal of female villains in media and movies has evolved significantly, as evidenced through the lens of Stuart Hall's representation theory and film analysis concepts. Traditionally confined to one-dimensional roles perpetuating gender stereotypes, contemporary cinema showcases multi-dimensional characters like those in Cruella, challenging societal norms and defying traditional gender expectations. By employing narrative and non-narrative film analysis techniques, these characters are revealed as agents of subversion and empowerment, embodying a new archetype of female villains characterized by individual agency and autonomy. However, despite this progress, the lingering impact of gender stereotypes persists, influencing how female villains are depicted on screen. Thus, ongoing critical analysis and advocacy for more diverse and authentic representations of women in media remain crucial.